Jesus on Trial - Penny Frank; John Haysom (UK USA Lion Publishing, 1987)
Describes Jesus's arrest, trial, and crucifixion.
Australia
GB8622504 bnb
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Bible stories, English -- Gospels; Theology